Adaptive-robust friction compensation in a hybrid brake-by-wire actuator. (November 2014) - de Castro, Ricardo; Todeschini, Fabio; Araújo, Rui E; Savaresi, Sergio M; Corno, Matteo; Freitas, Diamantino
This work focuses on the development of a pressure-loop controller for a hybrid brake-by-wire system, composed of a hydraulic link and an electro-mechanical actuator. Towards this goal, we will start by constructing a reduced model that is capable of capturing the fundamental dynamics of the actuator, which is particularly useful for control design purposes. Motivated by the large friction disturbances that affect the system, we also investigate linear-in-the-parameter models suitable for (online) model-based friction compensation. More specifically, results from the theory of function approximation, together with optimization techniques, are explored to approximate the Stribeck friction model through a linear-in-the-parameter model. This new linear-in-the-parameter model is then employed in the design of a control law for tracking the braking pressure of the hybrid brake-by-wire. The main features of this controller are the robustness to parametric uncertainties, thanks to the inclusion of a switching- σ adaptive mechanism, and the attenuation of non-parametric disturbances with a continuous sliding mode action. The stability and robustness properties of the closed-loop system are investigated with the help of the Lyapunov method. Finally, experimental tests demonstrate the effectiveness of the proposed approach and its ability to handle disturbances.